Unsupervised feature extraction based on uncorrelated approach - Jayashree; Shiva Prakash, T.; Venugopal, K.R. (Information sciences, 2024)
In high-dimensional spaces, mathematically driven data processing methods have recently attracted a lot of attention. We consider the situation when information is obtained by sampling a probability distribution with support on or close to a sub-manifold of Euclidean space. In this paper, we provide an innovative unsupervised learning method called Uncorrelated Neighborhood Preserving Embedding (UNPE) which identifies the underlying manifold structure of a data set and preserves the neighborhood structure of the data set. We provide a concrete formulation with UNPE, an iterative technique to demonstrate the usefulness of the framework, which has been confirmed by experimental findings on datasets Coil20, Pie, Tox, and Prostate-GE that uses three different parameters viz., F-score, NMI, and accuracy. It is observed that performance is better than the LPP algorithm by 1%, PCA by 2%, and more than 2% of LLE and LE algorithms.